DYSTOCIA DUE TO FOETAL HYDROCEPHALUS AND PROGNATHISM IN A NON-DESCRIPT DOE - R. Kavin; R. M. Gowtham; S. Pradeep (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A one year old, non descript doe presented with the history of straining to deliver and hanging of ruptured water bag from the vulva was diagnosed as dystocia. The attempts for manual extraction of foetus were failed and a dead emphysematous male foetus was removed by caesarean section. Hydrocephalus and prognathism were observed in the dead foetus. The doe uneventfully recovered postoperatively.